Computation of Axisymmetric Turbulent Viscous Flow Around Sphere - Karim, M. M.; Rahman, M. M.; Alim, M. A. (Journal of Scientific Research, 2009)
Axisymmetric turbulent viscous flow around sphere is computed using finite volume method based on Reynolds-averaged Navier-Stokes (RANS) equations.Â Two-dimensional axisymmetric flow solver has been used to analyze flow at Reynolds number of 5Ã106. Spalart-Allmaras (S-A) and shear stress transport (SST) k-Ï turbulence models are used to capture turbulent viscous flow. The numerical results in terms of the skin friction coefficient, pressure coefficient and drag coefficient for different Reynolds numbers have been shown either graphically or in the tabular form. Velocity vectors have been displayed graphically. The computed results show good agreement with published experimental measurements. Keywords: Axisymmetric body of revolution; Sphere; Viscous drag; CFD; Turbulence model; Reynolds-averaged Navier-Stokes (RANS) equations. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i2.1286